Is viewing a painting like reading a story?: Trans-symbolic comprehension processes and aesthetic responses across two media. Issue 2 (7th February 2023) - Steciuch, Christian C.; Millis, Keith; Kopatich, Ryan D.
ABSTRACT: A large body of research has outlined how mental models are formed by comprehending texts, yet relatively less work has been conducted in the field of comprehending artworks. Trans-symbolic comprehension (TSC) processes have been theorized to partially account for how mental models are formed across media. The current study tested whether participants use these processes similarly across reading stories and viewing paintings. The current study also tested whether the frequencies of TSC processes predict the aesthetic responses of understanding, interest, and pleasure. Participants typed out their thoughts while viewing paintings and reading texts. The think-aloud protocols were then parsed and coded for TSC processes. Results indicated similarities in TSC processes across both texts and paintings; however, the association between the TSC processes and aesthetic responses were greater for the texts than for the paintings. Overall, the results provide support for the TSC framework.